2006
DOI: 10.1097/01.aids.0000198094.23691.58
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of a proactive cellular telephone intervention for smokers living with HIV/AIDS

Abstract: These results suggest that individuals living with HIV/AIDS are receptive to, and can be helped by, smoking cessation treatment. In addition, smoking cessation treatment tailored to the special needs of individuals living with HIV/AIDS, such as counseling delivered by cellular telephone, can significantly increase smoking abstinence rates over that achieved by usual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 26 publications
5
134
3
Order By: Relevance
“…We could identify no specific smoking cessation interventions for HIV positive smokers at the onset of this study, although recently, a study comparing brief advice plus NRT to cell-phone-delivered counseling plus NRT was reported (Vidrine et al 2006). The cell phone intervention was found to be more effective than the brief advice condition (Vidrine et al 2006).…”
Section: Introductionmentioning
confidence: 80%
“…We could identify no specific smoking cessation interventions for HIV positive smokers at the onset of this study, although recently, a study comparing brief advice plus NRT to cell-phone-delivered counseling plus NRT was reported (Vidrine et al 2006). The cell phone intervention was found to be more effective than the brief advice condition (Vidrine et al 2006).…”
Section: Introductionmentioning
confidence: 80%
“…Future research should also develop smoking cessations for HIV-positive smokers. A few intervention studies have been published (e.g., Vidrine, Arduino, Lazev, & Gritz, 2006), and future efforts with this group should target medication adherence and depression as intervention components.…”
Section: Discussionmentioning
confidence: 99%
“…Participants receiving the cell phone intervention were significantly more likely to be abstinent at the 3-month follow-up compared to participants in the usual care condition (36.8% vs. 10.3%). Further details on the two-group randomized clinical trial comparing these interventions have been reported elsewhere (Vidrine, Arduino, Lazev, & Gritz, 2006). Demographic, health behavior, and psychosocial variables were collected at baseline and at 3-month follow-up.…”
Section: Methodsmentioning
confidence: 99%